Marts og April Maaned 1867. Agcrdyrkningsberetning. (Fra Begyndelsen af Mai.) - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Marts og April Maaned 1867. Agcrdyrkningsberetning. (Fra Begyndelsen af Mai.)